2023
DOI: 10.1007/s11739-023-03230-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling nutritional status score predicts 2-year outcomes in elderly patients admitted for acute heart failure

Abstract: Background Heart failure (HF) is a major cause of death among the elderly. Its prevalence increases dramatically with age. The prevalence of malnourished subjects is high in hospitalized elderly patients. We aimed to investigate the prognostic role of malnutrition, assessed by controlling nutritional status (CONUT) score, on adverse clinical outcomes in the elderly admitted for acute HF. Methods We enrolled 293 patients (mean age 84 years; 48% men) consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been reported that nutritional status should be assessed during heart failure treatment to predict heart failure prognosis [22,23]. Various studies have also shown that improving the nutritional status of heart failure patients can improve prognosis, prevent disease deterioration, and decrease patient mortality [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nutritional status should be assessed during heart failure treatment to predict heart failure prognosis [22,23]. Various studies have also shown that improving the nutritional status of heart failure patients can improve prognosis, prevent disease deterioration, and decrease patient mortality [24,25].…”
Section: Discussionmentioning
confidence: 99%